Abdurrahman Wahid: Antara Monisme dan Dualisme dalam Tasawuf - Mahmudi Mahmudi (Institut Ilmu Keislaman Annuqayah, 2015)
The term ‘Tasawuf Nusantara’ (archipelago’s sufism) gets influence from two major models of sufism order: falsafiyah order and sunniyah order. The former was popularly called as monoism, while the latter was dualism. This study is to formulate a conceptual framework of Abdurrahman Wahid (or mostly known as Gus Dur)’s idea on tasawuf. The typical ground of Gus Dur’s sufism is under analysis on the basis of both orders. This study uses a descriptive approch to research in order to address a fundamental question: which one of these two models of tasawuf that Gus Dur could be included? After gathering data, the conclusion of this study is that Gus Dur has been grounded in the monoism order which is later framed into islamic religiousity, indonesia nationality, and mistycal spirituality.